2018
DOI: 10.1016/j.cell.2018.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of the Conformational Dynamics of Single Influenza Hemagglutinin Trimers

Abstract: Influenza hemagglutinin (HA) is the canonical type I viral envelope glycoprotein and provides a template for the membrane-fusion mechanisms of numerous viruses. The current model of HA-mediated membrane fusion describes a static "spring-loaded" fusion domain (HA2) at neutral pH. Acidic pH triggers a singular irreversible conformational rearrangement in HA2 that fuses viral and cellular membranes. Here, using single-molecule Förster resonance energy transfer (smFRET)-imaging, we directly visualized pH-triggered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
176
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(192 citation statements)
references
References 56 publications
16
176
0
Order By: Relevance
“…The inferred movements of the HA heads to enable antibody H7.5 binding suggest that the HA1 head is "breathing", and this motion is reminiscent of conformational masking described for the HIV envelope glycoprotein (23)(24)(25). Indeed, a very recent study using single molecule FRET observed that H5 HA undergoes reversible conformational changes (26).…”
Section: Discussionmentioning
confidence: 93%
“…The inferred movements of the HA heads to enable antibody H7.5 binding suggest that the HA1 head is "breathing", and this motion is reminiscent of conformational masking described for the HIV envelope glycoprotein (23)(24)(25). Indeed, a very recent study using single molecule FRET observed that H5 HA undergoes reversible conformational changes (26).…”
Section: Discussionmentioning
confidence: 93%
“…Once triggered, this energetic imbalance ultimately results in the fusion protein undergoing an irreversible transition to the post-fusion state. Indeed many early pioneering studies on influenza HA led to the development of the "spring-loaded" mechanistic model for viral membrane fusion that is the prevailing way in which these machines are considered to function [21][22][23][24][25][26][27][28][29][30][31][32]. In this model, type I fusion proteins function analogous to taut springs that are poised in a high energy state that, once triggered, rapidly and irreversibly "spring" or refold to the low-energy, post-fusion state.…”
mentioning
confidence: 99%
“…As shown above, CSOP has the potential to be a broadly useful tool for investigating diverse biological processes including protein isoform changes during cell differentiation (51), modifications in glycan height during cancer progression (26), and kinetics of protein conformation changes (52). Ongoing developments in protein labeling strategies using antibodies and site-specific chemical labels have the potential to improve the ability of CSOP to quantify the height and flexibility of cell surface molecules and their physiological impacts.…”
Section: Discussionmentioning
confidence: 99%